Earthquake‐affected development of a travertine ridge. Issue 1 (11th December 2013) - Gradziński, Michał; Wróblewski, Wojciech; Duliński, Marek; Hercman, Helena
Abstract: Although the relation between travertine and tectonics is commonly accepted, the influence of seismic activity on the internal structures and facies development of travertine has not been examined extensively. The aim of this paper was to unravel the impact of seismic shocks on the anatomy of a travertine mound. Dreveník travertine in the Central Western Carpathians of Slovakia was studied using detailed facies analysis, based on fieldwork coupled with microscope and stable isotope studies. The travertine formed a ridge fed by ascending water of deep circulation, charged with CO2 of geogenic origin. The location of the ridge over an impermeable Palaeogene flysch complex and the stable isotope composition of the travertine support the above interpretation. The ridge is composed of crystalline crust travertine, lithoclast travertine, fine‐grained lithoclast travertine, paper‐thin raft travertine and coated bubble travertine. The travertine underwent brittle deformations resulting in formation of fissures and intraclast breccia. Several lines of evidence prove that the deformations occurred during travertine deposition: (i) breccias are covered by undisturbed layers of travertine; (ii) ground fissures are filled with younger travertine; and (iii) calcite filling fissures and cementing breccia crystallized from water with the same isotopic composition as the travertine. The deformations resulted from seismic shocks which also triggered rockfall avalanches that led to the destruction of the upper part of the travertine slope and deposition of lithoclast travertine on its lower parts. Local hydrological conditions changed after the shocks, favouring ponding of water which, in turn, led to formation of paper‐thin raft travertine over lithoclast travertine. Thus, earthquakes exerted an important control on the development of the studied travertine mound. It is plausible that earthquakes have impacted other travertine mounds and influenced their facies development.